Novel Caffeic Acid Nanocarrier: Production, Characterization, and Release Modeling. (10th November 2013) - Fathi, Milad; Mirlohi, Maryam; Varshosaz, Jaleh; Madani, Golnoosh
Abstract : This paper deals with the development of novel nanocarriers using layer by layer carbohydrate coating of caffeic acid loaded solid lipid nanoparticles (SLNs) to improve stability and colon delivery of the poorly water-soluble caffeic acid. Three biopolymers (chitosan, alginate, and pectin) in different concentrations (0.1, 0.25, and 0.5%) were electrostatically coated over the SLN surface. The size and zeta potential of produced nanocarriers were measured using photon correlation spectroscopy. Mathematical models (i.e., zero-order, first-order, Higuchi, Ritger-Peppas, reciprocal powered time, Weibull, and quadratic models) were used to describe the release and kinetic modeling in gastrointestinal solution (GIS). Also, antioxidant activity of caffeic acid during the release in GIS was investigated using DPPH and reducing activity methods. The prepared treatments coated by alginate-chitosan as well as pectin-chitosan coated SLN at the concentration of 0.1% showed nanosized bead; the latter efficiently retarded the release of caffeic acid in gastric media up to 2.5 times higher than that of SLN. Zeta potential values of coated samples were found to significantly increase in comparison to SLN indicating the higher stability of produced nanocarriers. Antioxidant activity of caffeic acid after gastric release did not result in the same trend as observed for caffeic acid release from different treatments; however, in line with less caffeic acid release in the intestine solution by the effect of coating, lower antioxidant activity was determined at the end stage of the experiment.